BAHASA KIASAN DALAM KUMPULAN LAGU RATU SIKUMBANG - Rahmi Noviade; Hasnah Faizah; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study entitled Language Allegories in Ratu Sikumbang set of songs. This study aimed to describe the types of figurative language and meaning contained in Ratu Sikumbang set of songs. This research uses descriptive method. The object of this study is figurative language and meaning of figurative language. The data source is the object of this study are the songs contained in a collection of songs Ratu Sikumbang. This research process qualitative data. To obtain the data and document engineering researchers conducted a study or library. Data in the form of lyrics that correspond to figures of speech in Ratu Sikumbang set of songs. Data obtained using qualitative analysis techniques and validity of the data obtained with the technique of the adequacy of reference, discussion and triangulation. Ratu Sikumbang collection of songs produced by Agri'e and Al-Glory. A collection of songs Ratu Sikumbang totaling 53 songs. The results of this study are as follows. (1) The types of figurative language found amounted to 102 the data; 5 metaphors, hyperbole 24, 24, parable, allegory 22, 9 parable, fable 1, 2 personification, one epithet, 1 sinekdoke, 2 metonymy, antonomasia 9, 1 1 hipalase and satire. The specificity of figurative language used every song lies in the use of words that come from the environment, and the words derived from the expression of feelings of the author; (2) The meanings of figurative language that amounted to 102, has diverse meanings based on the use of figurative language found in the collection of the song Ratu Sikumbang. The meaning of life in the form of hardship, heartbreak, insults and expression of love to the mother. The specificity of meaning used by the composer lies in the use of figurative language from the natural surroundings containing social and cultural dimensions of West Sumatra.Keywords: Figuratively Language, Meaning, set of songs